BANGUNAN UNTUK BERNAFAS SOLUSI POLUSI UDARA DI JAKARTA - Kenzo Therin; J.M. Joko Priyono Santosa (Jurusan Arsitektur dan Perencanaan, 2021)
This Breathing Building Project which is located on Jl. The pioneer, Mega Kuningan, is a project that is expected to be able to solve the problem of air pollution in the area architecturally. This project is a building that implements a natural air exchange system using plant media to absorb carbon dioxide gas produced by motor vehicle emissions. This building also aims as a pioneer project in Jakarta to be an inspiration and reference for future designers in solving air problems from an architectural perspective. The problem that I think is happening in the city of Jakarta at this time is that there are no projects that aim to reduce the level of air pollution in Jakarta. This can be seen from the minimal number of environmentally friendly facilities that can be used in general. It can also be seen from the buildings in Jakarta which are